"You Can't Always Get What You Want" — Linearity as the Golden Ratio of Toxicology. Issue 4 (1st October 2014) - Bast, Aalt; Hanekamp, Jaap C.
Referring to the Golden Ratio (i.e. expressed in the Fibonacci sequence) in nature and art, we conclude that toxicology knows its own Golden Ration, namely linearity. The latter seems imposed on pharmaco-toxicological processes that in fact show far more complexity than simple linearity could hope to elucidate. Understanding physiological and pharmaco-toxicological processes as primarily linear is challenged in this contribution based on very straightforward principles and examples.